Ecological specialization and morphological diversification in Greater Antillean boas (2016)
Colonization of islands can dramatically influence the evolutionary trajectories of organisms, with both deterministic and stochastic processes driving adaptation and diversification. Some island colonists evolve extremely large or small body sizes, presumably in response to unique ecological circumstances present on islands. One example of this phenomenon, the Greater Antillean boas, includes both small (<90 cm) and large (4 m) species occurring on the Greater Antilles and Bahamas, with some islands supporting pairs or trios of body?size divergent species. These boas have been shown to comprise a monophyletic radiation arising from a Miocene dispersal event to the Greater Antilles, though it is not known whether co?occurrence of small and large species is a result of dispersal or in situ evolution. Here, we provide the first comprehensive species phylogeny for this clade combined with morphometric and ecological data to show that small body size evolved repeatedly on separate islands in association with specialization in substrate use. Our results further suggest that microhabitat specialization is linked to increased rates of head shape diversification among specialists. Our findings show that ecological specialization following island colonization promotes morphological diversity through deterministic body size evolution and cranial morphological diversification that is contingent on island? and species?specific factors.